Uporabniški vmesniki sistemov za poizvedovanje in uporabniška prijaznost - Vilar, Polona (Knjižnica, 2008)
The paper deals with the characteristics of user interfaces of information retrieval systems with the emphasis on design and evaluation. It presents users' information retrieval tasks and the functions which are offered through interfaces. Design rules, guidelines and standards are presented, as well as criteria and methods for evaluation. Special emphasis is placed on the concept of user friendliness as one of the most important characteristic of the user interfaces. Various definitions of user friendliness are presentedand their elements are also discussed. In the end, the paper shows how user interfaces should be designed, taken into consideration all these criteria.
Keywords: uporabniški vmesniki; informacijski sistemi; računalniški sistemi; poizvedovanje; načrtovanje